Peran Pendidikan Islam dalam Resolusi Konflik Sosial dan Moral di Indonesia - Rizal Fathurrohman (Nusantara: Jurnal Pendidikan Indonesia, 2022)
In Indonesia, there are still many Islamic educational institutions that do not emphasize intercultural education. This makes social conflicts even more difficult to resolve because they are considered part of a religious vocation. From this background, this study aims to examine the role of Islamic education in the resolution of social and moral conflicts in Indonesia. This study uses a qualitative approach with an analytical descriptive method, and the tool used is a literature study. The findings of this study indicate that Islamic education responds to social and moral conflicts in Indonesia as a development of diverse (multicultural) ideals so that there are no social and moral disputes regarding traditions in all sectors of Indonesian society. So it is necessary to revitalize the process of transforming the value of Islamic education by prioritizing the elements of 1) rational and functional understanding of religion and 2) the need for an attitude of pluralism that is fostered thru intellectual and humanistic Islamic education. Thus, Islamic education can be a valuable tool in the process of social interaction if it is based on universal religious principles.